FORMATION OF FUTURE READYNESS OF TEACHERS TO LOCAL HISTORY WORK WITH STUDENTS AS PEDAGOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2002)
In this article, different approaches to the definition of the concept "readiness" are analyzed in the psycho-pedagogical literature. The investigation phases, essence, structural components, and conditions of creation of the student's readiness for the profession's activity are considered. The definition of the concept "readiness of the students for carrying out on learning the work of local lore" is given.